ON THE ISSUE OF DEPORTATION OF THE PEOPLES OF THE NORTH CAUCASUS TO KAZAKH SSR IN THE YEARS OF THE GREAT PATRIOTIC WAR (ACCORDING TO KAZAKH ARCHIVES) - Aagan, Burkitbaj Gelmanuly (History, Archeology and Ethnography of the Caucasus, 2023)
The paper aims to collect and systemize the data of the Kazakh archives on placement, keeping and features of the stay of the deported peoples of the North Caucasus on the territory of Kazakhstan. The author limited the scope of research to residents of the republics of the North Caucasus, since the largest number of deportations were from Karachay-Cherkessia and Chechen-Ingushetia republics. Consideration of all aspects of the deportation of Crimean Tatars, Greeks from the Crimean Autonomous Republic, Meskhetian Turks, Khemshins from Georgia requires separate research. The object of the author’s research was the issues of deportation, accommodation and keep of the peoples of the North Caucasus in 1944 to Kazakhstan. On the basis of a scientific analysis of the materials of a number of archival documents – various resolutions, directives, certificates, reports, the author traces the processes of resettlement and control over the arriving representatives of the deported peoples. The resettled families were specially distributed by the authorities to various regions of the vast territory of the republic. A considerable number of deportees ended up in political camps set up at factories, or were sent to build complex engineering structures. When conducting a scientific analysis, the author of the article used data from documents from Kazakhstani archives and collections of documents on the subject. As the main materials of the study, party documents, directives of the NKVD bodies, materials from the archives of the Prosecutor General’s Office, the Ministry of Internal Affairs and the KNB of the Republic of Kazakhstan were involved. The author reveals that the very Stalinist policy of deportation of peoples was carried out on the basis of the narrow framework of party instructions of the Bureau of the Central Committee of the All-Union Communist Party of Bolsheviks. All these resolutions and instructions are found everywhere in investigation cases or indictments found by the author in archival funds. The main results of the study are the identification of valuable documentary information on such issues as the definition of the regions of Kazakhstan involved in the resettlement process, indicating the number of resettled, the conditions of detention and adaptation of the deported.